2013
DOI: 10.1182/blood-2011-01-331819
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interaction between Kit and Scl

Abstract: Key Points

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…Comparison of the transcriptomes of murine SCL-LMO1-induced T-ALLs and of their normal counterparts points to the regulation of apoptosis as a top gene ontology category among SCL targets (Supplemental Figure 10A). We observed that 2-ME2 induced apoptosis in vitro both in pre-LSCs and in T-ALL blasts from SCL tg LMO1 tg mice (Supplemental Figure 10B), consistent with an inhibition of SCL antiapoptotic function (49)(50)(51).…”
Section: -Me2 Kills Leukemic Blasts Without Affecting Viability Of Nsupporting
confidence: 71%
See 3 more Smart Citations
“…Comparison of the transcriptomes of murine SCL-LMO1-induced T-ALLs and of their normal counterparts points to the regulation of apoptosis as a top gene ontology category among SCL targets (Supplemental Figure 10A). We observed that 2-ME2 induced apoptosis in vitro both in pre-LSCs and in T-ALL blasts from SCL tg LMO1 tg mice (Supplemental Figure 10B), consistent with an inhibition of SCL antiapoptotic function (49)(50)(51).…”
Section: -Me2 Kills Leukemic Blasts Without Affecting Viability Of Nsupporting
confidence: 71%
“…The percentages of cell viability are shown (right panel, n = 6, *P ≤ 0.05). IC 50 pre-LSCs ( Figure 2A). We found that MS5-DL4 lo cells sustained viability of SCL tg LMO1 tg pre-LSCs more efficiently than MS5 expressing higher DL4 levels ( Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…tg mice was performed essentially as previously described [119]. Bone marrow cells were depleted of lineage positive cells through immunomagnetic bead cell separation (LIN -) and plated in suspension culture in IMDM with 15% FCS, 100 ng/mL murine Steel Factor (SF), 10 ng/mL human IL-6, 100 ng/ml human IL-11 and 5 ng/mL murine IL-3, at a concentration of 1610 6 cells/mL.…”
Section: Lmo1mentioning
confidence: 99%